Analysis of Malondialdehyde Level in Leprosy Patients - Pane, Ria S; Lubis, Syahril R; Darmi, Mila (International Journal of Innovative Research in Medical Science, 2018)
Background: Leprosy is a chronic disease caused by Mycobacterium leprae. Oxidative stress (OS) is a condition associated with an increased rate of celluler damage induced by the oxygen derived oxidants commonly known as reactive oxygen species (ROS). ROS are capable of damaging celluler constituen generated in excess during the chronic, inflammatory, and neurodegenerative disease process of leprosy. Malondialdehyde (MDA) is end product of lipid peroxidation by ROS and serves as marker of celluler damage. Aim: To analyse the diference of MDA level in Paucibacillary (PB) and Multibacillary (MB) leprosy. Methods: 17 new cases of leprosy patients that were diagnosed by clinical and laboratory examinations. We conducted blood samplings and measurements of plasma MDA level with HPLC method. Results: In this study, there was increased the mean of MDA level in MB compared with PB and significant statistically (p<0, 05). Conclusion: Tissue damage due to OS in leprosy patients is more severe in MB group than PB group